2017
DOI: 10.1007/s10147-017-1210-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of Twist1, Snail1 and squamous cell carcinoma antigen for the prognostic evaluation of invasion and metastasis in cervical squamous cell carcinoma

Abstract: Combined detection of Twist1 and Snail1 in SCCA-positive biopsy specimens may be a potential method for evaluating the invasion and metastasis of CSCC prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The multivariable logistic regression analysis showed that LVI, DI, TS, and SCC antigen level were independent risk factors, which is also consistent with previous reports ( 4 , 21 23 ). LVI is closely associated with LNM in CC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The multivariable logistic regression analysis showed that LVI, DI, TS, and SCC antigen level were independent risk factors, which is also consistent with previous reports ( 4 , 21 23 ). LVI is closely associated with LNM in CC.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the rate of LNM was 0.00% in patients with no LVI, a DI <1/2, and a TS <2 cm (low-risk group) according to the RPA. The negative LVI, less tumor size and less depth of invasion meant the less invasion in the intravascular system and parametrial involvement, leading to the less possibility of LNM ( 21 23 , 30 ). Lymphadenectomy may be avoided in these patients to reduce postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated pretreatment SCC Ag level is associated with a more advanced stage [79], larger primary tumor size [7, 9, 10], regional nodal involvement [7, 8, 11, 12], and lymphovascular [8, 12] and deep stromal [8] infiltration in patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid double-modality treatment, surgery should only be offered to patients with a low likelihood of undergoing adjuvant CCRT or radiotherapy. Pretreatment SCC Ag was associated with postoperative indications for adjuvant radiotherapy in patients with cervical cancer [8, 12, 20]. Reesink-Peters et al reported that in those with early-stage cervical cancer and elevated pretreatment SCC Ag levels (> 1.9 ng/ml), 57% of patients at FIGO stage IB1 and 74% of patients at FIGO stage IB2/IIA had postoperative indications for adjuvant radiotherapy; in contrast, among those with normal pretreatment SCC Ag levels, 16% of patients at FIGO stage IB1 and 29% of patients at FIGO stage IB2/IIA had indications.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of cell migration and invasion capacity is associated with malignant progression and poor prognosis of CC [ 26 ]. To evaluate the effects of MAGI3 on migration and invasion of CC cells, MAGI3 was ectopically expressed in HeLa (HPV18 positive) and C‐33A (HPV18 negative) CC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%